Prevalence and determinants of the dangerous selfie among medical and nursing students: a cross-sectional study from eastern India - Priyamadhaba Behera; Arvind Kumar Singh; Vikas Bhatia; P. S. Preeti; Rishav Kumar; Satyajeet Das; Rupesh Tholia; Ritajyoti Ghosh; Sandeep Kumar; K. S. Safiya; Rojismita Purohit; Raman Bansal (BMC, 2020)
Abstract Background Globally, there has been an exponential rise in smartphone use and selfie taking among youth. To make selfies exciting, dangerous selfies are often taken that may lead to catastrophic consequences, including death. This study aims to estimate the prevalence of dangerous selfies and to determine the factors associated with dangerous selfies among medical and nursing students in India. Methods The study was conducted at the All India Institute of Medical Sciences (AIIMS), Bhubaneswar, India, in April-August 2018. The inclusion criteria were students enrolled in the Bachelor of Medicine and Bachelor of Surgery (MBBS) and nursing courses of AIIMS, Bhubaneswar. Students who did not use smartphones were excluded from the study. The interview schedule and Selfitis Behaviour Scale (SBS) were used to collect information on sociodemographic variables, smartphone use and variables related to selfies and dangerous selfies. Forward stepwise logistic regression was undertaken with the probability of entry and removal as 0.05 and 0.10, respectively. Results Of 633 eligible participants, 595 were included in the study. The mean (SD) age of the participants was 21.2 (1.6) years. More than half (56.8%) of the participants were female, 384 (64.5%) were medical students and 211 (35.5%) were nursing students. Nearly two-thirds of the participants (70.6%) preferred to take selfie. One hundred thirty three (40.3%) of the participants posted selfies on social media daily. The prevalence of dangerous selfies was 8.74% (95% CI: 6.73-11.28). Eight injury episodes while taking selfies were reported by seven (1.2%) participants. Being male (AOR 4.96, 95% CI 2.53-9.74), posting selfies on social media daily (AOR 3.33, 95% CI 1.71-6.47) and an SBS score > 75 (AOR 4.97, 95% CI 1.43-17.28) were independent predictors of dangerous selfies. Conclusion Nearly one in ten medical and nursing students reported having taken a dangerous selfie, and one in one hundred reported having been injured while attempting to take a selfie. Being male, posting selfies on social media daily and an SBS score > 75 were independent predictors of dangerous selfies. Further research is required to identify the community burden of dangerous selfies and to develop strategies to prevent selfie-related fatalities among youths.